Housing real estate economics and finance - Rita Yi Man Li (Journal of Risk and Financial Management, 2022)
Housing research is one of the hot topics in many countries. This paper provides a quick review of the housing economics research in the US, Sweden, Latvia, China, Corsica, and Italy published in this special issue. Bao and Shah studied the effects of home-sharing platforms in general and the effects of the US' Airbnb on neighbourhood rent. Wilhelmsson's results showed that interest rates directly affected house prices and indirectly affected bank loans in Sweden. Caudill and Mixon threw light on the relative negotiating power of the buyer and seller as a key element of real estate price models. éCirjevskis presented a real application of 'step-by-step' valuation options for real estate development projects as a managerial risk management tool for similar real estate development projects in the EU to make investment decisions during COVID-19 and in the post-COVID-19 era. Pelizza and Schenk-Hoppé used an exponential Ornstein-Uhlenbeck process to model price dynamics provincially and regionally to estimate the liquidation value.
Keywords: 330; housing economics; housing finance; home-sharing; investment; real estate price; mortgage; bank loans